2004
DOI: 10.1023/b:pham.0000036920.50291.5b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stabilized Dynorphin Derivatives for Suppressing Tolerance in Morphine-Dependent Rats

Abstract: [N-Met-Tyr1]-Dyn A(1-13) amide showed significant stability and antinociceptive activity in the tail-flick test, thus pointing to the clinical potential of this derivative in the management of pain as well as its potential activity in suppressing opiate tolerance and withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Dyn A-(1-13) analogs that have been stabilized to metabolism at the N-and C-termini by incorporation of either an N-MeTyr and/or C-terminal amide, respectively, have also been evaluated in vivo (117,118). These analogs enhanced morphine analgesia in morphine-tolerant rats following both intravenous and pulmonary delivery, with effects observed for up to 3.4 and 4.4 h, respectively, after administration of [N-MeTyr 1 ]Dyn A-(1-13) amide by these two routes.…”
Section: Dynorphin a Analogs And Other Kor Peptides Studied In Vivomentioning
confidence: 99%
“…Dyn A-(1-13) analogs that have been stabilized to metabolism at the N-and C-termini by incorporation of either an N-MeTyr and/or C-terminal amide, respectively, have also been evaluated in vivo (117,118). These analogs enhanced morphine analgesia in morphine-tolerant rats following both intravenous and pulmonary delivery, with effects observed for up to 3.4 and 4.4 h, respectively, after administration of [N-MeTyr 1 ]Dyn A-(1-13) amide by these two routes.…”
Section: Dynorphin a Analogs And Other Kor Peptides Studied In Vivomentioning
confidence: 99%
“…In a previous study, 17 the metabolic stability of N-and C-terminal modifications of Dyn A (1-13) derivatives in human plasma was investigated and it was reported that one of the derivatives, N-MT Dyn A amide, showed a half-life in human plasma that was more than 100 times longer than that of Dyn A(1-13). The same study revealed on a qualitative level that these modifications remained pharmacologically active.…”
Section: Discussionmentioning
confidence: 99%
“…17 Among the peptides tested, [N-Met-Tyr 1 ]-Dynorphine A(1-13) amide (N-MT Dyn A amide) proved to be the most stable derivative, with a halflife of more than 2 hours (130 minutes) in vitro. 17 Previous studies using Dyn A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) showed that the activity of dynorphins was affected by their route of administration. Activity was observed after intravenous and intrathecal administration, but not intracerebroventricular or subcutaneous administration in morphine-dependent mice and rats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations